Total femoral replacement: a challenging but promising limb salvage option - Gaitán-Lee, Hernando; Peña Restrepo, Santiago; Suárez Jiménez, Luis José; Guzmán Nalus, Felipe; Piñeros Rincón, Mariana (International Journal of Research in Orthopaedics, 2023)
Total femur replacement is a limb salvage surgery indicated for patients with oncological and non-oncological pathologies of the femur. Given the characteristics of the patients, there are essential perioperative considerations such as the previous treatment with chemotherapy or radiotherapy, prevention of thromboembolic events, hemorrhage management, and booking of an intensive care unit. As demanding as the surgical technique is, preventing extensive fibrosis, major bleeding, acetabular defects, and changes in normal anatomy is possible. The complications described include infection, structural failure, tumor progression, aseptic loosening, and soft tissue failure. Functional results and survival vary from series to series, but reports exist as high as 70% at ten years.